The Influence of Photoperiod on the Action of Exogenous Leptin on Gene Expression of Proinflammatory Cytokines and Their Receptors in the Thoracic Perivascular Adipose Tissue (PVAT) in Ewes - Krawczyńska, Agata; Herman, Andrzej P.; Antushevich, Hanna; Bochenek, Joanna; Wojtulewicz, Karolina; Zięba, Dorota A. (Mediators of Inflammation, 2019)
Leptin resistance is either a condition induced by human obesity or a natural phenomenon associated with seasonality in ruminants. In the cardiovascular system, the leptin resistance state presence is a complex issue. Moreover, the perivascular adipose tissue (PVAT) appears to be crucial as a source of proinflammatory cytokines and as a site of interaction for leptin contributing to endothelium dysfunction and atherosclerosis progression. So the aim of this study was to examine the influence of the photoperiod on the action of exogenous leptin on gene expression of selected proinflammatory cytokines and their receptors in thoracic PVAT of ewe with or without prior lipopolysaccharide (LPS) stimulation. The experiment was conducted on 48 adult, female ewes divided into 4 group (n=6 in each): control, with LPS intravenous (iv.) injection (400 ng/kg of BW), with leptin iv. injection (20 μg/kg BW), and with LPS and 30-minute-later leptin injection, during short-day (SD) and long-day (LD) seasons. Three hours after LPS/control treatment, animals were euthanized to collect the PVAT adherent to the aorta wall. The leptin injection enhanced IL1B gene expression only in the LD season; however, in both seasons leptin injection intensified LPS-induced increase in IL1B gene expression. IL1R2 gene expression was increased by leptin injection only in the SD season. Neither IL6 nor its receptor and signal transducer gene expressions were influenced by leptin administration. Leptin injection increased TNFA gene expression regardless of photoperiodic conditions. Only in the SD season did leptin treatment increase the gene expression of both TNFα receptors. To conclude, leptin may modulate the inflammatory reaction progress in PVAT. In ewe, the sensitivity of PVAT on leptin action is dependent upon the photoperiodic condition with stronger effects stated in the SD season.